Accelerated Depreciation, Default Risk and Investment Decisions - Paolo Panteghini; Sergio Vergalli (Center for Economic Studies and ifo Institute (CESifo), 2016)
In this article we focus on a representative firm that can decide when to invest under default risk. On the one hand, this firm can benefit from generous tax depreciation allowances, on the other hand it faces a default risk. Our aim is to study the effects of tax depreciation allowances in a risky environment. As will be shown in our numerical analysis, generous tax depreciation allowances lead to a decrease in a firm's leverage and, in most cases, cause a reduction in default risk. This result has a strong policy implication, in that it shows that an investment stimulus pack is expected neither to increase the default risk nor to cause financial instability.
Keywords: H20; 330; capital structure; contingent claims; corporate taxation and hybrid securities